(untitled) (Revista de Física Médica, 2011)
Intraoperative radiotherapy allows the administration of a high radiation dose, in a single session, to an exposed tumor or a surgical site. Radiation is delivered by means of a set of applicators, where each applicator has a set of bevels with different angles. The dosimetric characterization of the set of applicators and bevels requires the performance of a large number of measurements. In this work, we present a procedure for the dosimetric characterization of a set of intraoperative radiotherapy applicators that significantly reduces the number of dosimetric measurements required, while preserving a satisfactory level of accuracy when compared to the complete series of measurements which in principle would be required.